A Sarong for Clio : Essays on the Intellectual and Cultural History of Thailand-Inspired by Craig J. Reynolds - Reynolds, Craig J.; Peleggi, Maurizio (Book collections on Project MUSE., 2015)
A Sarong for Clio testifies to an ongoing intellectual dialogue between its ten contributors and Craig J. Reynolds, who inspired these essays. Conceived as a tribute to an innovative scholar, dedicated teacher, and generous colleague, it is this volume's ambition to make a concerted intervention on Thai historiography--and Thai studies more generally--by pursuing in new directions ideas that figure prominently in Reynolds's scholarship. The writings gathered here revolve around two prominent themes in Reynolds's scholarship: the nexus of historiography and power, and Thai political and business cultures--often so intertwined as to be difficult to separate. The chapters examine different types of historical texts, Thai political discourse and political culture, and the media production of consumer culture.